Nike Apteros: Images of the Wingless Deity in Literature, Sculpture, Vase Painting and Numismatics - Kushnet, Marvin W. (KOINON: The International Journal of Classical Numismatic Studies, 2025)
The very concept of a form of Nike without wings is counterintuitive, but apteros is the epithet given to the Temple of Athena Nike situated on the Acropolis in Athens. As a graduate student decades ago, the author was introduced to the Temple of Athena Nike Apteros, meaning without wings, an image which ran counter to everything ever considered, for of course, Nike indeed had wings. However, this was not necessarily the case at Athens. There she was closely linked with Athena, and the resulting amalgamation was wingless as depicted in a wooden cult statue, long ago lost. This raises two questions: are there images of other types of the Wingless Victory extant, and are there ancient sources for Nike Apteros other than Pausanias? The original cult statue was reportedly wingless but not unique, as review of the literature has produced other examples of wingless Nikai which are few and not necessarily well explained. Rather than solely concentrating on the Athena Nike syncretism, this paper serves to identify and document additional representations of wingless forms of Nike as demonstrated in literature, by sculpture, painting and, in particular, by coinage. The varied appearance of Nike on the coins of Terina has been the subject of conflicting interpretations regarding the interrelationship of the eponymous nymph, the goddess, the and the Italian city. This review also serves to explain these differences and to survey past scholarship.